SECURITY POLICY COMPLIANCE IN PUBLIC INSTITUTIONS: AN INTEGRATIVE APPROACH - Koloseni, Daniel; Lee, Chong Yee; Lee, Gan Ming (Journal of Applied Structural Equation Modelling, 2018)
The success of organizational information security policies depends on employee’s continuous compliance from the time when it was first introduced into the organization. Hence, the purpose of this study is to investigate continuous compliance with information security policy among public organizations. Data were collected from 265 employees working in Tanzania public organizations. Data analysis employed a Structural Equation Modelling (SEM) approach. The study found that the effects of organizational commitment, perceived susceptibility and perceived severity have a positive influence on employee’s continuance intention to comply with security policies, while perceived barriers have a negative influence. Moreover, the effects of perceived benefits, self-efficacy, cues and information security awareness have no significant influence. Based on these findings, recommendations were given. There is a paucity of empirical research which investigates key issues that may influence information security policy continuous compliance in organizations. This study addresses this research gap, by integrating the Health Belief Model (HBM) with employee’s organizational commitment and information security awareness constructs to investigate information security policy continuance compliance in organizations.